A practical guide to managing cardiopulmonary toxicities of tyrosine kinase inhibitors in chronic myeloid leukemia - Kaddoura, Rasha; Dabdoob, Wafer A.; Ahmed, Khalid; Yassin, Mohamed A. (Frontiers in Medicine, 2023)
Tyrosine kinase inhibitors (TKIs) have revolutionized the treatment of chronic myeloid leukemia (CML). Still, their use is associated with various serious cardiopulmonary toxicities, including vascular adverse events, QT prolongation, heart failure, pleural effusion, and pulmonary arterial hypertension. The current fully approved TKIs (imatinib, bosutinib, dasatinib, nilotinib, and ponatinib) have different efficacy and safety profiles. The underlying mechanisms for cardiopulmonary toxicities are not fully known, but on- and off-target effects may be partly responsible. Imatinib has the most favorable safety profile among TKIs. Nilotinib and ponatinib were associated with vascular occlusive adverse events, whereas dasatinib was with pleural effusion and PAH. QT prolongation was mainly linked to third-generation agents. TKI-induced adverse events can lead to serious morbidities if left untreated. Unfortunately, dedicated clinical management guidelines for TKI-induced toxicities are not available. This review aims to discuss TKI-associated cardiopulmonary toxicities and proposes a practical guide to their management.